2011
DOI: 10.1002/bio.1269
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence studies of decomposition of ceric sulfate

Abstract: . Using such techniques we show that the thermal decomposition of both monoclinic and bCe(SO4)2·4H2O in air at 500°C leads to the formation of cerous sulphate. Use of various atmospheres (air/N2/vacuum) and temperature profiles for the decomposition by the different researchers may be responsible for the discrepancies between literature results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…29,30 The weight loss of Pt 1.0% /SCe-I and Pt 0.1% / SCe-R samples between 600 and 800 °C was 2.68 and 0.58%, respectively, which was attributed to the decomposition of sulfate species on the catalyst surface. 31 This phenomenon may be due to the further elution of sulfate or the reaction between NaOH and sulfate in the reduction process, resulting in less sulfate in the Pt 0.1% /SCe-R sample. What was more, the tiny weight loss of Pt 1.0% /SCe-I and Pt 0.1% /SCe-R samples below 350 °C (2.83 and 3.00%) demonstrated that the catalysts were stable in the temperature range of the denitration activity test.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…29,30 The weight loss of Pt 1.0% /SCe-I and Pt 0.1% / SCe-R samples between 600 and 800 °C was 2.68 and 0.58%, respectively, which was attributed to the decomposition of sulfate species on the catalyst surface. 31 This phenomenon may be due to the further elution of sulfate or the reaction between NaOH and sulfate in the reduction process, resulting in less sulfate in the Pt 0.1% /SCe-R sample. What was more, the tiny weight loss of Pt 1.0% /SCe-I and Pt 0.1% /SCe-R samples below 350 °C (2.83 and 3.00%) demonstrated that the catalysts were stable in the temperature range of the denitration activity test.…”
Section: Resultsmentioning
confidence: 99%
“…In order to study the thermal stability of metal-supported sulfated cerium oxide samples, TG analysis is shown in Figure b. The weight loss of Pt 1.0% /SCe-I and Pt 0.1% /SCe-R samples at 50–159 °C was 1.64 and 2.05%, respectively, which can be attributed to the desorption and dehydroxylation of surface adsorbed water. , The weight loss of Pt 1.0% /SCe-I and Pt 0.1% /SCe-R samples between 600 and 800 °C was 2.68 and 0.58%, respectively, which was attributed to the decomposition of sulfate species on the catalyst surface . This phenomenon may be due to the further elution of sulfate or the reaction between NaOH and sulfate in the reduction process, resulting in less sulfate in the Pt 0.1% /SCe-R sample.…”
Section: Resultsmentioning
confidence: 99%
“…31,32 In addition, MnPt/SCe and NiPt/SCe samples exhibited weight losses of 2.46% and 2.58% at 600-800 1C, which could be attributed to the decomposition of the sulfate species on the catalyst surfaces. 33 These samples maintained their structural stability up to 600 1C, suggesting that they can maintain operational stability at reaction temperatures of up to 350 1C. Furthermore, the NiPt/SCe sample showed a stronger water affinity, therefore, it might be more sensitive to water vapor during the NH 3 -SCR process than its MnPt/SCe counterpart.…”
Section: Crystal Structurementioning
confidence: 87%
“…Compounds CeF 3 , CeBO 3 are other examples . Even some hydrated salts of cerium show strong emission . However, CeAlO 3 does not fluoresce.…”
Section: Introductionmentioning
confidence: 99%
“…[21] Even some hydrated salts of cerium show strong emission. [23,24] However, CeAlO 3 does not fluoresce. Concentration quenching occurs due to energy transfer between similar ions and finally to a killer site.…”
Section: Introductionmentioning
confidence: 99%